2007
DOI: 10.1002/art.22903
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of exercise and effects of exercise on symptoms, function, aerobic fitness, and disease outcomes of rheumatoid arthritis

Abstract: Objective. To determine the effects of participation in a low-impact aerobic exercise program on fatigue, pain, and depression; to examine whether intervention groups compared with a control group differed on functional (grip strength and walk time) and disease activity (total joint count, erythrocyte sedimentation rate, and C-reactive protein) measures and aerobic fitness at the end of the intervention; and to test which factors predicted exercise participation. Methods. A convenience sample of 220 adults wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
170
2
7

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(186 citation statements)
references
References 39 publications
7
170
2
7
Order By: Relevance
“…We also found, similar to other published studies, that many individuals with RA have very low levels of physical activity (10,11) in spite of the demonstrated safety of exercise and published guidelines recommending physical activity for persons with RA (12). Although studies have examined the impact of exercise interventions on RA outcomes, most have focused on pain or function (13)(14)(15)(16)(17). Two recent systematic reviews found that physical activity did have beneficial effects on fatigue (18,19), but most exercise interventions have been resource intensive, requiring specially trained personnel, highly structured activities, and/or attendance at classes or a specified facility.…”
Section: Introductionsupporting
confidence: 87%
“…We also found, similar to other published studies, that many individuals with RA have very low levels of physical activity (10,11) in spite of the demonstrated safety of exercise and published guidelines recommending physical activity for persons with RA (12). Although studies have examined the impact of exercise interventions on RA outcomes, most have focused on pain or function (13)(14)(15)(16)(17). Two recent systematic reviews found that physical activity did have beneficial effects on fatigue (18,19), but most exercise interventions have been resource intensive, requiring specially trained personnel, highly structured activities, and/or attendance at classes or a specified facility.…”
Section: Introductionsupporting
confidence: 87%
“…Supervised exercise and 60-minute exercise sessions performed biweekly or less had a greater effect on quality of life than home-based exercises and 30-minute exercise sessions performed more than 3 times per week, respectively. Similarly, Neuberger et al showed that patients taking part in a 12-week class exercise program experienced significant amelioration in disease-related parameters, whereas home-based exercise did not have that result, probably because patients in this group exercised at a lower intensity (29). Indeed, most of the studies reporting positive effects of exercises on quality of life were supervised intervention trials (3,20,24), whereas most of the studies in which this outcome was not modified were home-based exercises (25).…”
Section: Discussionmentioning
confidence: 98%
“…Nine studies, including 228 patients in the intervention group and 209 patients in the control group, evaluated joint count. The Ritchie Articular Index was reported in 2 trials (5,23), swollen joint count in 2 studies (21,27), tender joint count in 2 studies (26,28), and both swollen and tender joint counts in 3 studies (8,22,29) (see Supplementary Table 3, available in the online version of this article at http://www3.interscience.wiley.com/journal/77005015/ home). Intervention tended to provide a positive effect on this outcome, although the difference did not reach the statistical significance (SMD 0.14 [95% CI Ϫ0.05, 0.33], P ϭ 0.14; I 2 ϭ 0%) (Figure 4).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Romatoid artritli hastaların da egzersize katılımında engelleyici faktörler olarak yorgunluk ve egzersizin yararı konusunda bilgi eksikliği bulunmuştur (49). Sosyal destek ve hastalık öncesindeki egzersiz alışkanlıkları, egzersize katılımı etkileyen faktörler olarak bildirilmiştir.…”
Section: Romatoid Artritunclassified